SORPTION AND DISPERSION OF STRONTIUM RADIONUCLIDE IN THE BENTONITE-QUARTZ-CLAY AS BACKFILL MATERIAL CANDIDATE ON RADIOACTIVE WASTE REPOSITORY - Herry Poernomo (Universitas Gadjah Mada, 2010)
The experiment of sorption and dispersion characteristics of strontium in the mixture of bentonite-quartz, clay-quartz, bentonite-clay-quartz as candidate of raw material for backfill material in the radioactive waste repository has been performed. The objective of this research is to know the grain size effect of bentonite, clay, and quartz on the weight percent ratio of bentonite to quartz, clay to quartz, bentonite to clay to-quartz can be gives physical characteristics of best such as bulk density (rb), effective porosity (e), permeability (K), best sorption characteristic such as distribution coefficient (Kd), and best dispersion characteristics such as dispersivity (a) and effective dispersion coefficient (De) of strontium in the backfill material candidate. The experiment was carried out in the column filled by the mixture of bentonite-quartz, clay-quartz, bentonite-clay-quartz with the weight percent ratio of bentonite to quartz, clay to quartz, bentonite to clay to quartz of 100/0, 80/20, 60/40, 40/60, 20/80, 0/100 respectively at saturated condition of water, then flowed 0.1 N Sr(NO3)2 as buffer solution with tracer of 0.05 Ci/cm3 90Sr as strontium radionuclide simulation was leached from immobilized radioactive waste in the radioactive waste repository. The concentration of 90Sr in the effluents represented as Ct were analyzed by Ortec b counter every 30 min, then by using profile concentration of Co and Ct, values of Kd, a and De of 90Sr in the backfill material was determined. The experiment data showed that the best results were -80+120 mesh grain size of bentonite, clay, quartz respectively on the weight percent ratio of bentonite to clay to quartz of 70/10/20 with physical characteristics of rb = 0.658 g/cm3, e = 0.666 cm3/cm3, and K = 1.680x10-2 cm/sec, sorption characteristic of Kd = 46.108 cm3/g, dispersion characteristics of a = 5.443 cm, and De = 1.808x10-03 cm2/sec can be proposed as candidate of raw material of backfill material in the radioactive waste repository.